Assessment of Hazardous Gaming in children and its dissimilarities and overlaps with Internet Gaming Disorder - Kewitz, Sonja; Leo, Katharina; Rehbein, Florian; Lindenberg, Katajun (Frontiers in Psychiatry, 2023)
Background and aims. Children have been vastly overlooked in Internet Gaming Disorder (IGD) and Hazardous Gaming research so far. The diagnoses are listed in different ICD-11 chapters (addiction vs. problematic health condition) and are thus considered as distinct constructs. However, screening tools for children do not exist yet. We aimed to investigate the psychometric properties of an existing IGD screening tool modified to also assess Hazardous Gaming in children. Further, we aimed to compare the dissimilarity and overlap between (subclinical) IGD and Hazardous Gaming in children.Methods. The study analysed data from a mixed school and clinical sample. Data from N = 871 children were analysed, including children between 8 and 12 years of age (M = 10.3, SD = 0.90). Data were collected via the Video Game Dependency Scale (CSAS) in its parent report version, which was adapted to assess Hazardous Gaming symptoms in addition to the IGD symptoms. Item analyses, reliability and factor analyses were conducted on the Hazardous Gaming version.Results. The results show that the adapted CSAS version which to assesses Hazardous Gaming symptoms in children, shows mostly shows acceptable psychometric properties. Explorative Factor Analysis (EFA) shows a 2-factor structure with one factor of higher order. Additionally, results show that 35.2 % of all children meeting the threshold for Hazardous Gaming exclusively meet criteria for Hazardous Gaming but not for (subclinical) IGD. Vice versa, 91.3 % of children with IGD also meet criteria for Hazardous Gaming.Discussion. Hazardous Gaming and (subclinical) IGD are distinct constructs with some overlaps and might have a temporal relation. We recommend adding four items to assess Hazardous Gaming using the CSAS and further evaluate the validity. The assessment of Hazardous Gaming in children is crucial because it might occur in much younger age groupsearlier than subclinical or full-syndrome IGD.